2014
DOI: 10.3390/su6129027
|View full text |Cite
|
Sign up to set email alerts
|

Profit Analysis and Supply Chain Planning Model for Closed-Loop Supply Chain in Fashion Industry

Abstract: Abstract:In recent decades, due to market growth and use of synthetic fiber, the fashion industry faces a rapid increase of CO2 emission throughout the production cycle and raises environmental issues in recovery processing. This study proposes a closed-loop supply chain (CLSC) structure in fashion industry and develops its planning model as multi-objective mixed integer linear programming to find an optimal trade-off between CLSC profit and CO2 emission. The planning model is associated with the profit analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Packaging reduction [18,25,43] Product recycling [18,19] Green process design [50] Eco-labelling [1,25,50,51] Biological textile production [51] Replacement of solvent-based polyurethane with water-based alternatives [19] Compliance Verification of sustainable manufacturing processes [51] Process certification [1,25,50,51] Transport Decrease in the volumes shipped by ocean and air [9] Reverse logistic systems [43] Social Labour Practices & Decent Work…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Packaging reduction [18,25,43] Product recycling [18,19] Green process design [50] Eco-labelling [1,25,50,51] Biological textile production [51] Replacement of solvent-based polyurethane with water-based alternatives [19] Compliance Verification of sustainable manufacturing processes [51] Process certification [1,25,50,51] Transport Decrease in the volumes shipped by ocean and air [9] Reverse logistic systems [43] Social Labour Practices & Decent Work…”
Section: Methodsmentioning
confidence: 99%
“…A major progress was observed in closed-loop SCs (CLSC). It was revealed that an efficient design of CLSC could not only mitigate environmental pollutions generated throughout the SC, but also increase economic benefits [50].…”
Section: Sustainability Integration In the Supply Chainmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings show that gaps in literature exists concerning the use of MCDM approaches to support inventory management decisions with respect to economic and environmental criteria. Reverse logistics is considered in 27 publications, while only 11 papers combined forward and reverse logistics to support decision making in a closed-loop supply chain (Govindan et al 2016a;Garg et al 2015;Ghayebloo et al 2015;Mota et al 2015;Devika et al 2014;Kannegiesser and Gunther 2014;Oh and Jeong 2014;Pishvaee et al 2014;Ozkir and Basligil 2013;Paksoy et al 2012;Quariguasi Frota Neto et al 2010). Only few of the papers dealing with modelling material flows in a closed-loop supply chain presents a case study with realistic data.…”
Section: Decision Problemsmentioning
confidence: 99%